International volunteering in a changing aidland. Issue 12 (19th October 2017) - Schech, Susanne
Abstract: The growing diversity of North – South international volunteerism challenges the widely accepted distinction between volunteering for development as a long‐standing component of official development assistance and the more recent phenomenon of volunteer tourism as a private sector led commercial endeavour focused primarily on the personal growth of the volunteer. This paper reviews recent research that blurs this distinction by placing international volunteering within the geographical imaginaries of development and the neoliberal practices of governance of aidland. It focuses on four themes tackled in recent research: i) the ways in which neoliberal ideologies have shaped the motivations, goals, practices and governance of international volunteering; ii) the contexts in which international volunteering can foster more equitable relationships between Northern and Southern development actors; iii) what roles emotion and affect play in these relationships, and iv) the extent to which international volunteering can offer a critical perspective on the rules, logics and ideologies of aidland. The main argument is that while neoliberal conceptualisations of development have evidently shaped international volunteering, they do not fully capture the relational and experiential impacts of volunteering. The technologies of proximity afforded by volunteering can lead to critical and transformative insights into development and aidland, particularly when volunteers are embedded in local organisations over a longer time.